The role of algebra and its application in modern sciences - Juraev, Davron Aslonqulovich; Bozorov, Murot Nashvandovich (Engineering Applications, 2024)
This work deals with the emergence of Algebra and its applications in technical and engineering problems. Algebra becomes important in school when we learn to work with variables, expressions and equations. At first glance, it seems that these are abstract concepts that we will never need in real life. However, in practice, we constantly encounter situations where it is necessary to apply knowledge of algebra to solve problems and make important decisions. One example of algebra being used in everyday life is financial planning. When creating a budget, calculating interest on a loan, or calculating investments, we use algebra to determine optimal strategies and predict future outcomes. Algebra also allows us to solve complex problems related to planning trips or purchasing goods, taking into account our financial capabilities. n addition, algebra has its applications in science and technology. It is the basis for developing algorithms, programming and working with large volumes of data. Thanks to algebra, computers, smartphones, the Internet, and many other technological achievements were created that have become an integral part of our lives.